Effectiveness of interferon-free therapy for the treatment of HCV-patients with compensated cirrhosis treated through the Irish early access program. (3rd June 2017) - Gray, E; O'Leary, A; Bergin, C; Cannon, M; Courtney, G; Crosbie, O; De Gascun, CF; Fanning, L J; Feeney, E; Houlihan, DD; Kelleher, B; Lambert, J S; et al.
ABSTRACT: Background : We investigated the real-world effectiveness of interferon-free regimens for the treatment of patients with compensated cirrhosis infected with hepatitis C virus (HCV). Method : Using the Irish national HCV treatment registry, the effectiveness and safety of interferon-free regimens for HCV-infected patients treated between April 2015 and August 2016, was determined. Results : A SVR12 was achieved in 86% of subjects treated with sofosbuvir/ledipasvir ± ribavirin (SOF/LDV±RBV), 93% treated with paritaprevir, ombitasvir and ritonavir combined with dasabuvir ± ribavirin (3D±RBV) and 89% treated with sofosbuvir/daclatasvir ± ribavirin (SOF/DCV±RBV). The discontinuation rate was 5% and the on-treatment mortality rate was 1%. Conclusion : The availability of interferon-free regimens represents a significant breakthrough for the treatment of HCV infection. Treatments options, with high SVR12 rates, are now available for patients with compensated cirrhosis who were unsuitable for treatment with interferon-based regimens. Data obtained from studies conducted in real world practice provide robust information fundamental for input into future economic evaluations for agents used for the treatment of HCV infection.